The quilombola occupation: “resistance recipe” of the Mãe Preta Territory (RS) - Flores, Luiza Dias (Revista de Antropologia, 2021)
This article presents part of the research material from my doctoral dissertation, developed with the Morada da Paz kilombola community, also known as the Territory of Mãe Preta. The community is located in the rural area of Triunfo, in the state of Rio Grande do Sul, and is formed mainly by black women. It is characterized by being a spiritual community that follows the guidelines of a preta velha, Mãe Preta, and an exu, Seu Sete. It was from the elders in the community, recognized as Yas and Baba, which I learned about the concept of occupation. The aim here is to recover this concept, presenting its singularities in relation to other understandings of occupation. Finally, I argue that, like the indigenous “retakes” and the “reclaim” of American neo-pagan witches, the occupation elaborated by Morada is also a “recipe for resistance” against colonial and capitalist attacks.